Two Year Longitudinal Change and Test-Retest-Precision of Knee Cartilage Morphology in a Pilot Study for the Osteoarthritis Initiative - Eckstein, Felix (2007)
OBJECTIVE: Fast low angle shot (FLASH) and double echo steady state (DESS) MRI sequences were recently cross-calibrated for quantification of cartilage morphology at 3 Tesla. In this pilot study for the Osteoarthritis Initiative we compare their test-retest precision and sensitivity to longitudinal change. METHOD: 9 participants with mild to moderate clinical OA were imaged at baseline, year 1 and year 2. Coronal 1.5mm FLASH and sagittal 0.7mm DESS sequences were acquired; 1.5mm coronal multiplanar reformats (MPR) were obtained from the DESS. Patellar, femoral and tibial cartilage plates were quantified in paired fashion, with blinding to time point. RESULTS: In the weight-bearing femorotibial joint, average precision errors across plates were 1.8% for FLASH, 2.6% for DESS, and 3.0% for MPR-DESS. Volume loss at year 1 was not significant; at year 2 the average change across the femorotibial cartilage plates was −1.7% for FLASH, −2.8% for DESS, and −0.3% for MPR-DESS. Volume change in the lateral tibia (−5.5%; p<0.03), and in the medial (−2.9%; p<0.04) and lateral femorotibial compartment (−3.8%; p<0.03) were significant for DESS. CONCLUSION: FLASH, MPR-DESS and DESS all displayed adequate test-retest precision. Although the comparison between protocols is limited by the small number of participants and by the relatively small longitudinal change in cartilage morphology in this pilot study, the data suggest that significant change can be detected with MRI in a small sample of OA subjects over 2 years.